The Relationship between the Sharecropping System, Informal Credit, and Productivity: The Empirical Evidence from the Madurese Traditional Solar Salt Business - Prihantini, Campina Illa; Hanani, Nuhfil; Asmara, Rosihan; Syafrial, Syafrial (Faculty of Fisheries and Marine Science, Brawijaya University, 2024)
The ease in obtaining a loan is often regarded as a key advantage of the sharecropping system in the traditional solar salt business of Pamekasan Regency. The challenges faced by tenant farmers in accessing formal financial institutions have led to the continued prevalence of the sharecropping system in rural areas. This research aims to find the relationship between the sharecropping system, informal credit, and salt land productivity. The first analysis employs a multiple linier regression model on 93 tenant farmers in Pamekasan Regency to analyze the factors that influenced the amount of informal credit. Next, a quantitative descriptive analysis was carried out regarding the relationship between the sharecropping system, the amount of informal credit, and the productivity of solar salt fields area. Findings indicate that the significant factors affecting the credit amounts requested by tenant farmers include the cost of funds, loan duration, profits garnered by tenant farmers, the availability of collaterals, and the presence of other credit sources. The second conclusion of this research findings is that the extent of solar salt land area has a positive correlation with the informal credit amount, as does the productivity of the land. It should be an expected necessity for the government to play a larger role in supplying formal credit to small-scale farmers. This includes measures like credit rationing to diminish the influence of landowners.